THE GENERAL APPROACH TO STRUCTURAL SYNTHESIS OF RAILWAY STATIONS - Safronenko, O. O. (Science and Transport Progress, 2008)
One of directions of improving the design process of railway stations is to realize a descending principle of design: from a block diagramme to a final design solution. In this article the general approach to a structural synthesis – the first design stage with such a principle of design – is given.